Avian haemosporidian infections in rufous-collared sparrows in an Andean dry forest: diversity and factors related to prevalence and parasitaemia. Issue 6 (26th December 2018) - Cadena-Ortiz, Héctor; Mantilla, Juan S.; de Aguilar, Juan Rivero; Flores, Diana; Bahamonde, Daniela; Matta, Nubia E.; Bonaccorso, Elisa
Abstract: Despite intensive research during the last few decades, understanding of ecological and physiological factors related to haemosporidian infections in birds is still fragmentary. Since more model organisms are needed in order to understand these infections in the wild, we analysed avian haemosporidian infections in the rufous-collared sparrow ( Zonotrichia capensis, Emberizidae) in a dry forest of the Ecuadorian Andes. Parasite diversity was screened using molecular and morphological approaches. By molecular diagnosis, we identified three linages that were phylogenetically placed in the context of molecular haemosporidian diversity and associated with a morphospecies. By microscopy, we identified five described morphospecies and one additional undescribed morphospecies. We found that avian haemosporidian prevalence on the study site was 76.3%. Additionally, we used a series of generalized linear models to explore the potential relationship of parasite prevalence and parasitaemia with a set of variables related to physiological and environmental conditions. Although our results revealed associations of haemosporidian infections with precipitation, age and sampling site, the models only explained a small fraction of the variation.